Social reintegration of cisgender and transgender women post-incarceration in Brazil: policies and challenges - Miranda, Raquel B. (2024)
Background: Social reintegration relies on the support given to prisoners not only during their reentry into society but also throughout their imprisonment. Our goal was to analyze the expectations reported by cisgender and transgender women returning to society and of the justice and social welfare professionals from the Brazilian prison system.Methods: A qualitative analysis using saturation sampling was conducted. The participants were selected through a non-probabilistic sampling technique. Data was collected through semi-structured interviews with professionals involved in the management of the prison system and female former inmates. Interviews were transcribed and analyzed using an open and focused coding process. Textual data was stored, organized, and coded using Atlas software according to emerging themes.Results:The study involved 15 professionals and 13 female former inmates, five of them identified as transgender women. Among the professionals, the age range went from 38 to 65 years old; they reported a work history in their respective fields, from 10 to 35 years, with an equal distribution across genders. As for the female former inmates, their ages ranged from 24 to 42 years old, and the most reported crime was drug trafficking. Their incarceration time varied from 1 to 8 years. Female inmates were vulnerable to abuse and violence, including physical, sexual, and emotional violence. Women in situations of prior vulnerability faced additional challenges during their sentences. Transgender women were even more neglected and discriminated against by the system. Despite the professionals being aware and concerned about vulnerabilities and the need to improve the reintegration process, in general, they were not sensitive to the gender perspective. There were no specific policies able to support social integration for this public.Conclusions:Data showed multifaceted challenges faced by female former inmates within the Brazilian prison system, highlighting the insufficient policies for both cisgender and transgender women. Additionally, the results revealed a lack of sensitivity among professionals regarding gender issues and their particularities in the prison system and social reintegration. These findings emphasize the need for a more comprehensive and intersectional approach that addresses the diverse socio-economic backgrounds of these individuals.